A novel index, Chinese visceral adiposity index is closely associated with urinary albumin‐creatinine ratio in Chinese community adults, especially in hypertensive or hyperglycemic population: Results from the REACTION study. Issue 12 (29th November 2022) - Li, Binqi; Wang, Weiqing; Gao, Zhengnan; Tang, Xulei; Yan, Li; Wan, Qin; Luo, Zuojie; Qin, Guijun; Chen, Lulu; Ning, Guang; Mu, Yiming
Abstract: Background: The association between the Chinese Visceral Adiposity Index (CVAI) and urinary albumin to creatinine ratio (UACR) has not been illustrated. The current study aimed to investigate the association between CVAI and UACR and to compare the discriminative power of CVAI, triglyceride, body mass index (BMI), waist circumference (WC), and waist‐to‐hip ratio (WHR) with UACR in the Chinese community population. Methods: This study included 34 732 participants from the REACTION (Risk Evaluation of cAncers in Chinese diabeTic Individuals) study. Binary logistic regression analyses were performed to detect the association between CVAI, triglyceride, BMI, WC, WHR and UACR. Results: Binary logistic regression analysis showed that, after adjusting for potential confounders, in women, CVAI (odds ratio [OR]:1.16, 95% confidence interval [CI]: 1.01–1.34) and triglyceride (OR: 1.18, 95% CI: 1.04–1.33) were associated with UACR, whereas BMI, WC, and WHR were not associated with UACR; in men, CVAI (OR: 1.24, 95% CI: 1.02–1.50), WC (OR: 1.21, 95% CI 1.00–1.48), and triglycerides (OR: 1.18, 95% CI 0.97–1.44) were associated with UACR, whereas BMI and WHR were not associated with UACR. Stratified analysis showed that the correlation between CVAI and UACR was stronger in the population with 5.6 ≤ fasting blood glucose (FBG) <7.0 or 7.8 ≤ post‐load blood glucose (PBG) <11.1 mmol/L, FBG ≥7.0 or PBG ≥11.1, systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg. Conclusions: In the Chinese general population, CVAI and UACR were significantly associated in both genders. At higher CVAI levels, the population with prediabetes, diabetes, and hypertension has a more significant association between CVAI and UACR. Abstract : Highlights This is the first large‐sample, multicenter study of the relationship between Chinese Visceral Adiposity Index (CVAI) and urinary albumin to creatinine ratio (UACR) in Chinese community adults. CVAI and UACR were significantly associated in both genders. At higher CVAI levels, the population with prediabetes, diabetes, and hypertension has a more significant correlation between CVAI and UACR. 摘要: 背景:中国人内脏脂肪指数(CVAI)与尿白蛋白肌酐比(UACR)之间的关系尚未阐明。本研究旨在探讨CVAI与UACR之间的关系, 并比较CVAI、三酰甘油、体重指数(BMI)、腰围(WC)、腰臀比(WHR)对中国社区人群UACR的鉴别能力。 方法:本研究包括34732名来自REACTION研究的参与者。采用二元logistic回归分析检测CVAI、三酰甘油、BMI、WC、WHR和UACR之间的相关性。 结果:二元logistic回归分析显示, 在校正潜在混杂因素后, 女性CVAI(优势比[OR]:1.16, 95%CI: 1.01‐1.34)和三酰甘油(OR:1.18, 95%CI:1.04‐1.33)与UACR相关, 而BMI、WC、WHR与UACR无关；男性CVAI(OR:1.24, 95%CI:1.02‐1.50)、WC(OR:1.21, 95%CI:1.00‐1.48)和甘油三酯(OR:1.18, 95%CI:0.97‐1.44)与UACR相关, 而BMI、WHR与UACR无关。分层分析表明, 在5.6 mmol/L≤空腹血糖(FBG)<7mmol/L或7.8mmol/L≤餐后2小时血糖(PBG)<11.1mmol/L, FBG≥7.0mmol/L或PBG≥11.1mmol/L, 收缩压≥140 mmHg或舒张压≥90 mmHg的人群中, CVAI与UACR的相关性较强。 结论:在中国普通人群中, CVAI和UACR在两性中均显著相关。在较高的CVAI水平下, 糖尿病前期、糖尿病和高血压人群在CVAI和UACR之间具有更显著的相关性。